2018
DOI: 10.1111/jdi.12771
|View full text |Cite
|
Sign up to set email alerts
|

Renal function after intravitreal administration of vascular endothelial growth factor inhibitors in patients with diabetes and chronic kidney disease

Abstract: The present study aimed to determine whether intravitreal administration of vascular endothelial growth factor inhibitors is associated with deterioration of renal function, as seen with systemic administration, in patients with diabetes and chronic kidney disease. Estimated glomerular filtration rates before and after 160 intravitreal injections of vascular endothelial growth factor inhibitors (aflibercept, bevacizumab or ranibizumab) were compared in 69 patients with diabetes and with a baseline estimated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 14 publications
4
31
1
Order By: Relevance
“…In another study, diabetic patients accepted intravitreal anti-VEGF agents rapidly developed worsening proteinuria and renal function decline ( Hanna et al, 2019 ). On the contrary, a current study showed that the average eGFR did not change in a total of 69 diabetic patients who received intravitreal anti-VEGF agents ( Kameda et al, 2018 ). In addition, no episode of acute kidney injury occurred.…”
Section: The Role Of Vegf-a In Abnormal Angiogenesis Of Dncontrasting
confidence: 56%
See 1 more Smart Citation
“…In another study, diabetic patients accepted intravitreal anti-VEGF agents rapidly developed worsening proteinuria and renal function decline ( Hanna et al, 2019 ). On the contrary, a current study showed that the average eGFR did not change in a total of 69 diabetic patients who received intravitreal anti-VEGF agents ( Kameda et al, 2018 ). In addition, no episode of acute kidney injury occurred.…”
Section: The Role Of Vegf-a In Abnormal Angiogenesis Of Dncontrasting
confidence: 56%
“…The VEGF-A inhibitors have previously shown some beneficial effects on diabetic ocular disease and DN experimental mice models, but recent evidences raised controversial opinions on its use in clinical practice. Several lines of evidence revealed that patients accepted anti-VEGF treatment developed worsening proteinuria and glomerular microangiopathy ( Hanna et al, 2019 ; Touzani et al, 2019 ), while other studies supported that it is unlikely to cause any renal injury ( Kameda et al, 2018 ; O’Neill et al, 2019 ). Leucine-richα-2-glycoprotein 1 (LRG1) is a novel pro-angiogenic factor that has demonstrated to promote angiogenesis by enhancing ALK-1signaling pathway in both diabetic ocular disease and DN mouse models ( Wang et al, 2013 ; Haku et al, 2018 ; Hong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study of renal safety following acute anti-VEGF exposure showed no significant change in mean eGFR and no episodes of acute kidney injury, following a single intravitreal anti-VEGF injection of ranibizumab, aflibercept or bevacizumab, in a cohort of 69 patients with DM and CKD [29]. However, the study by Kameda and colleagues did not consider the potential cumulative effects of intravitreal anti-VEGF exposure on renal function.…”
Section: Discussionmentioning
confidence: 99%
“…70 A recent retrospective study of 69 patients did not report acute kidney injury after a short-term follow-up of 7 to 30 days after intravitreal injections of bevacizumab, aflibercept, or ranibizumab. 71 Levels of anti-VEGF agents and proteinuria were not monitored. This Japanese study also raised the possibility that differences in genetic background might modulate differences in renal toxicity among patients.…”
Section: Intravitreal Anti-vegf Administration: Systemic Absorptionmentioning
confidence: 99%